INFORMASI KINERJA KEMENTERIAN KESEHATAN BERDASARKAN REDESAIN PERENCANAAN DAN PENGANGGARAN - sumadiyah T olfah; Achmad Zunaidi; Risca Ardhyaningtyas (Direktorat Jenderal Anggaran Kementerian, Keuangan Republik Indonesia, 2023)
The implementation of the Planning and Budgeting System Redesign Policy (RSPP) is a policy that was rolled out to address the gap between planning and budgeting. This research was conducted to find out how far the RSPP policy has been implemented in ministries/agencies as a case study. Consideration of the Ministry of Health as a focus is one of the ministries with a large ceiling and has duties and functions that have a direct impact on the community. The research was conducted using mixed methods, namely quantitative (descriptive statistics related to the profile of planning and budgeting human resources) and qualitative (interviews related to the formulation of performance information as part of the RSPP policy implementation). The results of the research reveal that there are challenges and constraints in: 1) formulating the performance of the Ministry of Health; 2) the process of changing performance information between planning and budgeting documents (RKP, Ministry of Health Renja, and RKAKL). One reason is that human resources do not have a good understanding of the implementation of the RSPP and there are different perceptions regarding regulations. The results of this study can be used as a reference for increasing the effectiveness and suitability of planning and budgeting within the Ministry of Health.